2022
DOI: 10.3390/f13010091
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Morphological Features of Scots Pine Heartwood Formation in Two Forest Types in the Middle Taiga Subzone

Abstract: Currently, there is no consensus on how growing conditions affect the heartwood formation in Scots pine. Comparing the results obtained by different authors is difficult due to methodology differences and poor descriptions of the objects used. We selected two sample plots in (1) a blueberry pine forest on nutrient-rich and moist soil and (2) a lichen pine forest on nutrient-poor and dry soil and performed their detailed characterization. The sample plots were located 22 km apart in the middle taiga subzone (Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…While we estimated climatic conditions at the sampled plots using topographically derived variables, and found no significant correlations, other studies have indicated that climate can influence heartwood formation in both conifers [72,73] and angiosperms [74]. For teak (Tectona grandis) grown in India, wet sites yielded larger heartwood than dry sites [75], whereas the opposite case was found for teak planted in Ghana [76].…”
Section: Discussionmentioning
confidence: 68%
“…While we estimated climatic conditions at the sampled plots using topographically derived variables, and found no significant correlations, other studies have indicated that climate can influence heartwood formation in both conifers [72,73] and angiosperms [74]. For teak (Tectona grandis) grown in India, wet sites yielded larger heartwood than dry sites [75], whereas the opposite case was found for teak planted in Ghana [76].…”
Section: Discussionmentioning
confidence: 68%
“…We attempt to correlate structural observations on different xylem tissues with starch grains, water distribution, and nuclei availability ( Table 2 ). However, correlation did not explain the causes of HW formation involving many interconnected anatomical, chemical and physiological processes [ 18 , 23 , 53 ]. Future studies should track extractives across the xylem to better understand where extractives are formed.…”
Section: Discussionmentioning
confidence: 99%
“…The above studies indicate no sudden transition from SW to HW. Therefore, scientists present a theme focusing on the transition zone (TZ) between HW and SW in trees [ [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast color indicates higher extractive content, significantly improving the wood's natural durability. The degradation and incrustation of pores in the xylem vascular elements with extractive substances accompany heartwood formation, significantly reduce wood permeability, lead to water transport cessation, and prevent wood-decaying organism penetration [41][42][43]. Scented extractive substance contents in heartwood, namely, terpenoids (i.e., monoterpenoids and sesquiterpenes), are synthesized, accumulated, and shaped for fragrance formation [44].…”
Section: Introductionmentioning
confidence: 99%